Earthquake design practice for buildings - Booth, E. D. (ICE Publishing, 2014)
Earthquake Design Practice for Buildings, 3rd edition provides comprehensive, practical and easy to read advice for all engineers, designers and analysts of earthquake resistant structures. This new edition has been completely revised to account for the many developments that had taken place since the publication of the best-selling second edition.